2001
DOI: 10.1177/004947550103100119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HIV Infection on Presentation of Kaposi's Sarcoma

Abstract: We report a retrospective review of 57 patients with endemic Kaposi's sarcoma (EKS) seen between 1981 and 1990 and 40 prospectively diagnosed patients with and without human immunodeficiency virus (HIV) infection seen between 1991 and 1995. In the retrospective study 52 patients were males and five were females. Their ages ranged between 15 and 62 years with a mean of 39 years.Thirty-five (61%) patients had symptoms for more than 1 year. Nodular KS was seen in 75% of the patients. In the prospective study 26 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
2
9
2
Order By: Relevance
“…In keeping with the findings in other studies [15, 20, 3236], females in this study reported to health facilities at a significantly younger age than males. This could indicate that females were infected with HIV at an earlier age or that immunosuppression from HIV infection and Kaposi’s sarcoma pathogenesis progresses more rapidly in females.…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with the findings in other studies [15, 20, 3236], females in this study reported to health facilities at a significantly younger age than males. This could indicate that females were infected with HIV at an earlier age or that immunosuppression from HIV infection and Kaposi’s sarcoma pathogenesis progresses more rapidly in females.…”
Section: Discussionsupporting
confidence: 92%
“…It is currently not an uncommon finding in Nigeria, because the cumulative number of HIV infections is increasing yearly. The incidence of Kaposi's sarcoma in HIV‐infected patients treated at our institution is 3.3%, which is in the same range as that reported from the northern part of Nigeria by Ahmed et al 15 . During the period of this study, we treated 13 men and three women with AIDS‐associated Kaposi's sarcoma.…”
Section: Discussionsupporting
confidence: 77%
“…[2][3][4][5][6] Although rarely diagnosed before the emergence of HIV/AIDS, previous studies have documented the presence of EKS in Nigeria. 3,[7][8][9][10][11][12][13][14] In 1981, the emergence of KS among young gay men in New York, Los Angeles, and San Francisco heralded the beginning of the AIDS pandemic, 15,16 and since then, AAKS, an AIDS-defining disease, has emerged as the most commonly diagnosed malignancy among HIV-seropositive patients. 17 Other HIV-associated malignancies include non-Hodgkin's lymphoma and anal and cervical cancers, especially squamous intraepithelial lesions.…”
mentioning
confidence: 99%